The SNAP-25 gene is associated with cognitive ability: evidence from a family-based study in two independent Dutch cohorts - Gosso, M F; de Geus, E J C; van Belzen, M J; Polderman, T J C; Heutink, P; Boomsma, D I; Posthuma, D (Molecular psychiatry, 2006)
The synaptosomal-associated protein of 25 kDa ( SNAP-25 ) gene plays an integral role in synaptic transmission, and is differentially expressed in the mammalian brain in the neocortex, hippocampus, anterior thalamic nuclei, substantia nigra and cerebellar granular cells. Recent studies have suggested a possible involvement of SNAP-25 in learning and memory, both of which are key components of human intelligence. In addition, the SNAP-25 gene lies in a linkage area implicated previously in human intelligence. In two independent family-based Dutch samples of 391 (mean age 12.4 years) and 276 (mean age 37.3 years) subjects, respectively, we genotyped 12 single-nucleotide polymorphisms (SNPs) in the SNAP-25 gene on 20p12–20p11.2. From all individuals, standardized intelligence measures were available. Using a family-based association test, a strong association was found between three SNPs in the SNAP-25 gene and intelligence, two of which showed association in both independent samples. The strongest, replicated association was found between SNP rs363050 and performance IQ (PIQ), where the A allele was associated with an increase of 2.84 PIQ points ( P =0.0002). Variance in this SNP accounts for 3.4 % of the phenotypic variance in PIQ.